2017
DOI: 10.1007/s10047-016-0941-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a low initial cerebral oxygen saturation value in patients undergoing cardiac surgery

Abstract: Regional cerebral oximetry using near-infrared spectroscopy device, an INVOS 5100 C (Medtronic, Minneapolis, MN, USA), during cardiac surgery aims to avoid perioperative neurological impairment, especially during cardiopulmonary bypass. However, it is not uncommon to encounter critically low initial cerebral regional oxygen saturation or a low value unresponsive to intervention. Therefore, it is important to identify factors associated with low saturation value other than true cerebral hypoxia. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The ability of NIRS to identify patients at risk is not an unexpected finding, considering the fact that patient age is one of the variables used for EuroSCORE calculation, and at the same time rScO 2 baseline values decrease with increasing age. 15 However, it emphasises the importance of Table 4 Regional cerebral oxygen saturation (rScO 2 ) values for cardiac surgery patients with and without postoperative cognitive dysfunction (POCD) at discharge and at 3 monthsdlLow target MAP group. Median with (inter-quartile range) and tested with ManneWhitney U-test.…”
Section: Postoperative Cognitive Dysfunction At Dischargementioning
confidence: 99%
“…The ability of NIRS to identify patients at risk is not an unexpected finding, considering the fact that patient age is one of the variables used for EuroSCORE calculation, and at the same time rScO 2 baseline values decrease with increasing age. 15 However, it emphasises the importance of Table 4 Regional cerebral oxygen saturation (rScO 2 ) values for cardiac surgery patients with and without postoperative cognitive dysfunction (POCD) at discharge and at 3 monthsdlLow target MAP group. Median with (inter-quartile range) and tested with ManneWhitney U-test.…”
Section: Postoperative Cognitive Dysfunction At Dischargementioning
confidence: 99%
“…Previous studies reported that ScO 2 significantly correlated with Hgb, NTproBNP, eGFR, LVEF, age, and variables associated with body size [16, 17, 20, 21, 24]. To our knowledge, the current study was the first one that demonstrated a significant correlation between BNP and ScO 2 , although Heringlake et al reported that between NTproBNP and ScO 2 [24].…”
Section: Discussionmentioning
confidence: 49%
“…In line with these studies, Heringlake et al showed that ScO 2 significantly correlated with age, Hgb, N-terminal pro-brain natriuretic peptide (NTproBNP), estimated glomerular filtration rate (eGFR), and left ventricular ejection fraction (LVEF) [24]. ScO 2 values thus could be associated with risk factors, such as cardiac dysfunction [10, 19, 20, 21, 24], renal dysfunction [2124], age [24], and anemia [16, 17, 21, 24]. Consequently, Heringlake et al showed that the baseline ScO 2 could be predictive of morbidity and mortality after cardiac surgery [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to define a clinically relevant threshold of ScO 2 levels and the definition of cerebral desaturation assessed with NIRS is vague [31]. Patient characteristics, or intraoperative data including haematocrit, can possibly influence the ScO 2 readings [32,33]. We observed a comparable haemodilution during surgery for fluid responders and non-responders-obviously due to the administered fluid in each FC.…”
Section: Discussionmentioning
confidence: 73%